Heightened neural sensitivity to social exclusion in boys with a history of low peer preference during primary school - J. Susanne Asscheman; Susanne Koot; Ili Ma; J. Marieke Buil; Lydia Krabbendam; Antonius H.N. Cillessen; Pol A.C. van Lier (Developmental Cognitive Neuroscience, 2019)
Peer preference among classmates is a highly influential factor in children’s social development and not being preferred by peers has long-term consequences for children’s developmental outcomes. However, little is known about how a history of low peer preference during primary school is associated with neural responses to a new social exclusion experience in childhood. In this functional magnetic resonance imaging (fMRI) study, we examined self-reported social distress and neural responses to social exclusion using the Cyberball paradigm in primary school boys (Mage = 10.40 years) with a history of low (n = 27) versus high peer preference (n = 28). Boys were selected from a longitudinal classroom-based study in which children’s peer social preferences were assessed in three consecutive years prior to this study. Neuroimaging results showed that low peer preferred boys exhibited increased activation in the bilateral dorsolateral prefrontal cortex and right supramarginal gyrus during social exclusion as compared to high peer preferred boys. Increased neural activity was not accompanied by higher self-reported levels of social distress during social exclusion in low versus high peer preferred boys. Findings of this study may provide insight into the neural processes associated with real-life peer experiences in children attending primary school. Keywords: Peer preference, Social exclusion, Cyberball, Childhood, fMRI, dlPFC